(3RgQ GdBOGH hKeQ GdCdHGHs - (3EHQGgje Hf Ydj Hf Jeje GdCfUGQj, CHh ESMGb GdMUQj,J (B453 (3g` s ((3CMeO Hf YHOGdYRjR Hf Cjef GdYGeQi s)
(3ChdgG (B:s
(3bWYI ef QSGdI CLGH HgG GHhGdNWGH GdUGHi Yf CHj GdYHGS Hf SGHhQ GdeSJNQL Edi CHj GdNjQ Hf SHQg Yf QbYI hQOJ efg ai hUag Med GgOGg(B: (3hUdJ QbYJc aaVVJgG Yf NW eTQb s
(3BNQgG (B:s
(3hEfi hGSeGYjd jhe hOGYg dcG dZeQ jhe GdQhY aGQbg GdfUd aGf CZT KheG HYOge Gh CRQge acGdhMT jOfjgG ef GdbfU GdeMd CRQge s
(3cJH GdUaMI Gdhdi Hbde eZQHi eZGjQs
(3Jedc UdGM GdOjf GdUaOi GdeJhai (B764 (3g` HNWg HChdgG cPdc Jedc GHQGgje Hf LeGYg ef GdLgdGA eJhai (B790(3g`s
(3fSNI SGHYIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs